2015
DOI: 10.1051/0004-6361/201525872
|View full text |Cite
|
Sign up to set email alerts
|

Disentangling 2:1 resonant radial velocity orbits from eccentric ones and a case study for HD 27894

Abstract: Context. In radial velocity (RV) observations, a pair of extrasolar planets near a 2:1 orbital resonance can be misinterpreted as a single eccentric planet, if data are sparse and measurement precision insufficient to distinguish between these models. Aims. Using the Exoplanet Orbit Database (EOD), we determine the fraction of alleged single-planet RV detected systems for which a 2:1 resonant pair of planets is also a viable model and address the question of how the models can be disentangled. Methods. By simu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
35
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 33 publications
1
35
0
Order By: Relevance
“…Several studies have shown that the Keplerian signature of a single eccentric planet might also be fit with a model including two planets on circular (or nearly circular) orbits in 2:1 resonance, depending on the radial velocity accuracy and their time sampling (e.g., Anglada-Escudé et al 2010;Wittenmyer et al 2013;Kürster et al 2015). Numerous pairs of planets near the 2:1 orbital resonance have indeed be detected in transit with Kepler (e.g., Lissauer et al 2011;Delisle & Laskar 2014).…”
Section: Hip 109600mentioning
confidence: 99%
“…Several studies have shown that the Keplerian signature of a single eccentric planet might also be fit with a model including two planets on circular (or nearly circular) orbits in 2:1 resonance, depending on the radial velocity accuracy and their time sampling (e.g., Anglada-Escudé et al 2010;Wittenmyer et al 2013;Kürster et al 2015). Numerous pairs of planets near the 2:1 orbital resonance have indeed be detected in transit with Kepler (e.g., Lissauer et al 2011;Delisle & Laskar 2014).…”
Section: Hip 109600mentioning
confidence: 99%
“…Although PlanetPack and EXOFAST do provide (frequentist) statistics on the fits performed to the data, it is not straightforward to use those to compare different models, as all frequentist statistical measures assume an underlying null hypothesis which does not take into account either prior information nor the reality that there are more models than the one being tested. This is very important for complicated tasks such as calculating the evidence for additional planets in either the transits and/or the radial-velocities (especially in the case in which extra, non-planetary signals such as stellar activity might make this procedure even more difficult), or even for more simple but routine tasks such as finding evidence for an eccentric orbit (or even disentangling between significant eccentricity or additional planets; see e.g., Kürster et al 2015). Although this question has been explored in the literature for the detection of planets in radial-velocities (see, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…A Bayesian test with a physically motivated prior on eccentricity was devised by Lucy (2013). Also, Anglada-Escudé et al (2010), Wittenmyer et al (2013) and Kürster et al (2015) note that two planets in 2:1 mean motion resonances can appear as an eccentric planet, and propose ways to disentangle those cases. This problem has also been studied in Boisvert et al (2018); Nagel et al (2019); Wittenmyer et al (2019).…”
Section: Introductionmentioning
confidence: 99%